Seismic Response of a Historical Masonry Bridge under Near and Far-fault Ground Motions - Ozmen, Alper; Sayin, Erkut (Budapest Univ Technology Economics, 2021)
Historical masonry arch bridges which might be vulnerable to natural disasters are important part of the cultural heritage. Natural disasters, especially earthquakes can inflict damage to these structural systems. This paper aims to investigate a comparison of the effects of near and far-fault ground motions on the seismic response of masonry arch bridges under different earthquakes. Kalender masonry arch bridge which is located in Ergani, Turkey is selected as a numerical model. For this purpose, three-dimensional finite element model of the bridge is generated with ANSYS finite element software with macro modelling approach. Seismic response of the bridge is assessed by means of time-history analyses. The near-fault and far-fault ground motions, which have approximately equal peak ground accelerations, of 1979 Imperial Valley, 1999 Chi-Chi, 1999 Kocaeli and 2010 Darfield earthquakes are considered for the analyses. Comparisons between maximum displacements, maximum and minimum stress, which were acquired from the dynamic analyses of the masonry bridge subjected to each fault effect, are obtained. The study demonstrates that far-fault ground motions are as important as near-fault ground motions and it can be used together with near-fault ground motion for further evaluation of such historical masonry bridges.
Keywords: historical stone arch bridges; three-dimensional finite element method; dynamic analyses; near and far-fault ground motions; seismic response